Hubungan Antara Bahan Organik Sedimen Dengan Kelimpahan Makrozoobenthos Di Perairan Pantai Pandan Provinsi Sumatera Utara - Akmal Hawari; Bintal Amin; Efriyeldi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The study was conducted in August 2013 in the coastal waters of Pandan Beach North Sumatra Province. The method used in this study was a survey method. This study aims to determine the environmental condition of water, the type and abundance of macrozoobenthos, and its sediment organic matter relationships. makrozoobenthos abudance Sampling was designed by purposive sampling to collet macrozoobenthos by using 15x15 cm2 Ekman grab. The results showed the macrozoobenthos species found in the coastal waters of Pandan Beach composed of Anadara granosa, Cerithidea cingulata, Polymesoda expansa, Terebralia palustris, Turbo petholatus, Volema myristica, Telescopium telescopium, Nerita lineata, Hippopus porcellanus, Terebra maculata, and Terebralia sulcata. The macrozoobenthos abundance in the studied area ranged from 192,6-1,066.7 individuals/m2. The analysis of the sediment organic matter showed strong position relationships with macrozoobenthos abudance.Keywords: Organic,Sediment, Macrozoobenthos, Abundance, North Sumatera